IL-6 Amplifies TLR Mediated Cytokine and Chemokine Production: Implications for the Pathogenesis of Rheumatic Inflammatory Diseases - Caiello, Ivan (Public Library of Science, 2014)
The role of Interleukin(IL)-6 in the pathogenesis of joint and systemic inflammation in rheumatoid arthritis (RA) and systemic juvenile idiopathic arthritis (s-JIA) has been clearly demonstrated. However, the mechanisms by which IL-6 contributes to the pathogenesis are not completely understood. This study investigates whether IL-6 affects, alone or upon toll like receptor (TLR) ligand stimulation, the production of inflammatory cytokines and chemokines in human peripheral blood mononuclear cells (PBMCs), synovial fluid mononuclear cells from JIA patients (SFMCs) and fibroblast-like synoviocytes from rheumatoid arthritis patients (RA synoviocytes) and signalling pathways involved. PBMCs were pre-treated with IL-6 and soluble IL-6 Receptor (sIL-6R). SFMCs and RA synoviocytes were pre-treated with IL-6/sIL-6R or sIL-6R, alone or in combination with Tocilizumab (TCZ). Cells were stimulated with LPS, S100A8-9, poly(I-C), CpG, Pam2CSK4, MDP, IL-1β. Treatment of PBMCs with IL-6 induced production of TNF-α, CXCL8, and CCL2, but not IL-1β. Addition of IL-6 to the same cells after stimulation with poly(I-C), CpG, Pam2CSK4, and MDP induced a significant increase in IL-1β and CXCL8, but not TNF-α production compared with TLR ligands alone. This enhanced production of IL-1β and CXCL8 paralleled increased p65 NF-κB activation. In contrast, addition of IL-6 to PBMCs stimulated with LPS or S100A8-9 (TLR-4 ligands) led to reduction of IL-1β, TNF-α and CXCL8 with reduced p65 NF-κB activation. IL-6/IL-1β co-stimulation increased CXCL8, CCL2 and IL-6 production. Addition of IL-6 to SFMCs stimulated with LPS or S100A8 increased CXCL8, CCL2 and IL-1β production. Treatment of RA synoviocytes with sIL-6R increased IL-6, CXCL8 and CCL2 production, with increased STAT3 and p65 NF-κB phosphorylation. Our results suggest that IL-6 amplifies TLR-induced inflammatory response. This effect may be relevant in the presence of high IL-6 and sIL-6R levels, such as in arthritic joints in the context of stimulation by endogenous TLR ligands.